Analgesic Effect of Zolmitriptan Nanoparticles in Experimental Animal Models - Zadeh Khezri, Mr. Farshid Ali Naghi; Nargund, Dr. Shachindra L.; Lakshmi, Dr. C. S. R.; Nargund, Dr. L. V. G.; Alisani, Dr. Reza; Mohammadi, Azadeh (International Journal of Innovative Research in Medical Science, 2018)
Background: Zolmitriptan is used to treat migraine and certain other headaches. This study has been done to prepare specific Zolmitriptan Nano-nasal spray (Z-NPS) by ion gelation technique to evaluate the efficacy of analgesic activity of test drug as a nano nasal spray of Zolmitriptan (Z-NPS) and conventional preparation as a standard drug (Zolmist) against Nitro-glycerine induced migraine. The study was performed on mice by using hot plate method. Methods: In this study male Swiss albino mice weighing between 25-30 grams were taken and divided into 4 groups with 6 mice in each group. Zolmitriptan loaded chitosan nanoparticles (Z-NPS) was administered nasally (using specific inhalation mask) at a dose of 5 mg/kg and was compared with the control group which received water for injection and the standard drug Zolmitriptan (Zolmist) at a same dose in mice induced migraine using hot plate method. Reaction times were measured at 10, 20, 30 and 60 minutes after drug administration. Results: The test drug (Z-NPS) at a dose of 5 mg/kg after 10 minutes of drug administration showed an increase in the reaction time compared to the standard drug (Zolmist) at same dose of drug administration. However, Z-NPS showed significant increase in the reaction time after 10 minutes as compared to Zolmist. Conclusion: Zolmitriptan has significant analgesic properties in central-analgesic model i.e. Hot-plate method. The test drug could be used for anti-migraine activity.